The Professionalism of Islamic Religious Education Teachers in Improving The Spiritual Intelligence of Students At State Junior High School 1 Tungkal Ulu, Tungkal Ulu District, West Tanjung Jabung Regency, Jambi Province - Rosdalisa Rosdalisa; Hindun Hindun; Siti Raudatul Jannah (Dinasti International Journal of Education Management And Social Science, 2023)
The purpose of this study describes "Professionalism of Islamic Religious Education Teachers in Improving the Spiritual Intelligence of Students at 1 Tungkal Ulu Public Junior High School, Tungkal Ulu District, West Tanjung Jabung Regency, Jambi Province" which includes how the condition of students' spiritual intelligence, what are the professionalism efforts of PAI teachers in improve the spiritual intelligence of students, what about the results of the efforts that have been made by the PAI teacher in solving the obstacles faced to increase the spiritual intelligence of students. This research approach is qualitative. The method used is observation interviews and documentation. The data analysis is display reduction and conclusion drawing. The findings and analysis of the research are, 1) the condition of the spiritual intelligence of students at SMPN 1 Tungkal Ulu can be said to be lacking in spirituality. 2) Professionalism efforts made by PAI teachers in improving the spiritual intelligence of students include: carrying out yasiinan every Friday, midday prayers in congregation, group sholawat arts, organizing funerals, making infaq habits, PAI teachers must be an example of proper behavior for students, PAI teachers guide students in understanding the unpredictable life, PAI teachers encourage students to read the Qur'an and explain how its meaning is related to human life, PAI teachers provide enlightening anecdotes about spiritual personality to the class, as well as teachers PAI encourages students to discuss various topics from an Islamic point of view in class. 3) The results of the efforts that the PAI teacher has made in solving the obstacles faced to improve the spiritual intelligence of students at SMPN 1 Tungkal Ulu include: Student compliance, students always do assignments, are polite to teachers and friends, and are active in yasiinan activities.